Effect of Integrated Technologies on Production and Productivity of Pearl Millet in the Dryland Areas of Wag Himira Administrative Zone, Eastern Amhara, Ethiopia - Tafere Berhanu; Wubshet Beshir; Alemu Lakew (International Journal of Agronomy)
Production of pearl millet with yield improvement would have a direct impact on the drought-prone areas of Ethiopia since pearl millet is drought tolerant and early maturing with high water use efficiency. An experiment was conducted to study the performance of pearl millet under different technologies in 2013 and 2014 main cropping seasons at the main site of the research center, Aybra, with the objective of evaluating and identifying appropriate combinations of technologies that enhance the production of pearl millet in the study area. About fourteen integrated technologies were applied in a randomized complete block design with three replications. The analysis was done by using SAS software version 9.1, and means were separated through the Duncan multiple range test. Results of analysis of variance showed that yield-related traits of pearl millet were significantly influenced by the integration of technologies in the 2013 cropping season. According to the results, the maximum yield (3084 kg ha−1) was recorded with the application of the treatment combination of recommended fertilizer application + seed primming + tie ridging, while the minimum was recorded (919 kg ha−1) in the treatment combination of microdose application of fertilizer + primed seed + intercropping of pearl millet with mung bean. In the case of the 2014 cropping season, the highest grain yield (3687 kg ha−1) was recorded with the treatment combination of microdose fertilizer application + primed seed + tie ridging + intercropping of pearl millet with mung bean, whereas the lowest grain yield (2115 kg ha−1) was recorded in the treatment combination of no fertilizer application + primed seed + flat bed. Based on the results of the current investigation, it could be recommended that using technology integration of microdose, tied ridge, primed seed, and intercropping of pearl millet with mung bean is better to attain maximum yield in the study area and similar agroecologies.